3D tumor microtissues as an in vitro testing platform for microenvironmentally-triggered drug delivery systems. (15th July 2017) - Brancato, Virginia; Gioiella, Filomena; Profeta, Martina; Imparato, Giorgia; Guarnieri, Daniela; Urciuolo, Francesco; Melone, Pietro; Netti, Paolo A.
Graphical abstract: Abstract: Therapeutic approaches based on nanomedicine have garnered great attention in cancer research. In vitro biological models that better mimic in vivo conditions are crucial tools to more accurately predict their therapeutic efficacy in vivo . In this work, a new 3D breast cancer microtissue has been developed to recapitulate the complexity of the tumor microenvironment and to test its efficacy as screening platform for drug delivery systems. The proposed 3D cancer model presents human breast adenocarcinoma cells and cancer-associated fibroblasts embedded in their own ECM, thus showing several features of an in vivo tumor, such as overexpression of metallo-proteinases (MMPs). After demonstrating at molecular and protein level the MMP2 overexpression in such tumor microtissues, we used them to test a recently validated formulation of endogenous MMP2-responsive nanoparticles (NP). The presence of the MMP2-sensitive linker allows doxorubicin release from NP only upon specific enzymatic cleavage of the peptide. The same NP without the MMP-sensitive linker and healthy breast microtissues were also produced to demonstrate NP specificity and selectivity. Cell viability after NP treatment confirmed that controlled drug delivery is achieved only in 3D tumor microtissues suggesting that the validation of therapeutic strategies in such 3D tumor model could predict human response. Statement of Significance: A major issue of modern cancer research is the development of accurate and predictive experimental models of human tumors consistent with tumor microenvironment and applicable as screening platforms for novel therapeutic strategies. In this work, we developed and validated a new 3D microtissue model of human breast tumor as a testing platform of anti-cancer drug delivery systems. To this aim, biodegradable nanoparticles responsive to physiological changes specifically occurring in tumor microenvironment were used. Our findings clearly demonstrate that the breast tumor microtissue well recapitulates in vivo physiological features of tumor tissue and elicits a specific response to microenvironmentally-responsive nanoparticles compared to healthy tissue. We believe this study is of particular interest for cancer research and paves the way to exploit tumor microtissues for several testing purposes.